Determination of Dithiocarbamate Mancozeb Residues in Milk Samples Using GC-MS Method. Issue 6 (2nd November 2019) - Nageswara Rao, Tentu.; Cheedarala, Ravi Kumar
Abstract: The present study was performed to validate gas chromatography mass spectrometry analytical method for the determination of mancozeb residues in milk samples. The analytical method is based on the extraction procedure by using mineral acids. The extraction solution was sucked into the flask, the dripping funnel was quickly exchanged for the gas inlet. After 2 hours, the adsorption tube containing the isooctane was removed and closed. The solution was transferred into a sample vial and analysed using gas chromatography- mass spectroscopy (GC-MS). A Rxi-624Sil MS (30 m length x 0.32mm I.D. x 1.8 μm particle size capillary column is used for the separation. The method has linearity over the range 0.05 to 10.0 μg/mL. Recovery study was conducted at 0.05 and 0.5 mg/kg fortification levels. The average mean recoveries were calculated as 86.23 % at 0.05 mg/kg level and 92.69 % at 0.5 mg/kg level. The limit of quantification (LOQ) in milk was established as 0.05 mg/kg.